PEMANFAATAN PANAS BUANG DARI KENDARAAN BERTENAGA DIESEL UNTUK MENJALANKAN SISTEM REFRIGERASI ABSORPSI: SEBUAH TINJAUAN - Dyah Arum Wulandari; Nasywa Raihan Dhiyaulhaq (Jurnal Konversi Energi dan Manufaktur, 2022)
In Indonesia, refrigeration using Vapour Absorption Refrigeration System or absorption refrigeration system is still uncommon to be used in vehicles. This system is not like a vapor compression refrigeration system that uses electricity to run the compressor. Instead of it uses heat in the generator. The use of an absorption refrigeration system is considered to apply to vehicles that produce heat from the engine. This review article discusses the use of exhaust heat from several modes of transportation to cool the cabin or product through conceptual research by reviewing relevant literature. The results of this study indicate that a diesel-powered engine can generate sufficient heat to power the cooling system.